Impact of the COVID-19 Pandemic on Radiotherapy Supply - Francesco Tramacere; Artor Niccoli Asabella; Maurizio Portaluri; Corinna Altini; Cristina Ferrari; Lilia Bardoscia; Angela Sardaro (Radiology Research and Practice)
Background. The impetuous entrance of the COVID-19 pandemic in Italy in March 2020, after the onset and diffusion in China, found the health system widely unfit to face the large amount of infected patients. The matter of this investigation was to evaluate how pandemic fear and guidelines for limiting the diffusion of SARS-CoV-2 virus could have impacted the regular supply of radiotherapy (RT) and the outcome of the treatments. Materials and Methods. From March 9, 2020, to May 29, 2020, a register has been established to record patients that cancelled or postponed the RT appointment. The reasons were as follows: (1) patients whose appointments were postponed by the staff according to national guidelines; (2) patients who asked themselves to postpone the appointment; (3) patients who interrupted the treatment for causes directly or indirectly related to the pandemic; (4) patients who cancelled their care path. Results. A total number of 277 patients started regular RT, and 384 respected their computed tomography (CT) simulation appointment, but 60 of them had alteration of their therapeutic pathway. Among these, 18 cancelled their appointment. 42 patients asked to postpone their procedure. Twenty-seven out of 42 adduced directly or indirectly SARS-CoV-2 infection-related reasons. Conclusions. The COVID-19 pandemic affected the regular RT delivery to oncologic patients, owing to the delay or cancellation of procedures with the likely effect to observe worsening of local disease control and reduced survival rates in the future.